2020
DOI: 10.1088/1757-899x/713/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

A study on effectiveness of Building Information Modelling (BIM) on the Malaysian construction industry

Abstract: The introduction of Building Information Modelling (BIM) in Malaysia has been fairly recent and is gaining popularity. Although most literature have been focused on the adoption and application of BIM in Malaysia construction industry, the effectiveness of BIM has not been investigated. This study aims to investigate the influence of BIM on the Malaysian construction industry. A qualitative approach was taken and interviews were conducted with professionals with prior knowledge in both the construction industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 2 publications
0
25
2
Order By: Relevance
“…BIM provides solutions to the numerous problems such as building element clash, lack of collaboration between project team, inefficient information flow, inherent in the construction industry (Eastman et al, 2011;Latiffi et al, 2013;Kushwaha, 2016;Kong et al, 2020), with the dynamic nature of the construction industry to accommodate more challenges and complexity as the needs of the clients requires. For instance, BIM has made it easy for designers to easily spot clash of building elements by simply running clash detection analysis on the BIM model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIM provides solutions to the numerous problems such as building element clash, lack of collaboration between project team, inefficient information flow, inherent in the construction industry (Eastman et al, 2011;Latiffi et al, 2013;Kushwaha, 2016;Kong et al, 2020), with the dynamic nature of the construction industry to accommodate more challenges and complexity as the needs of the clients requires. For instance, BIM has made it easy for designers to easily spot clash of building elements by simply running clash detection analysis on the BIM model.…”
Section: Introductionmentioning
confidence: 99%
“…Latiffi et al (2013) also identified the implementation of BIM as a precursor to overcoming the following construction-related problems: delay, clash of design by different professionals and construction cost overrun. Similarly, Kong et al (2020) identified time, cost and design related issues. These identified challenges which not only affect developing countries, but developed economies have largely contributed to the lack of BIM adoption among the Nigerian construction professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Following that, the 2D system evolved into a computer-aided design (CAD) system Lattifi et al (2015). A CAD framework, according to Kong et al (2020), provides for the modeling of the building design process in three-dimensional (3D) space and the storage of architectural knowledge in the form of models and images. The CAD foundation will not be fully refined if non-graphic building details are generated using current graphics and models.…”
Section: Bim and The Industrymentioning
confidence: 99%
“…These objects should consist of geometric definitions and associated data rules, the geometry is integrated none redundantly, and the parametric rules should automatically modify associated geometries when inserted into a building model or when changes are applied to associated objects (Yin et al , 2020). Moreover, objects can be defined at hierarchy levels, the rules of the objects must automatically identify if a change to an object is feasible, and the objects must have the ability to link to or send and receive attributes (Kong et al , 2020). To implement BIM on a macro level, market and industry level, Succar et al (2012) stated that there must be a sufficient foundational framework suitable for the systematic investigation of the BIM domain.…”
Section: Theoretical Backgroundmentioning
confidence: 99%